Cultivating Cannabis in a paraguayan nature reserve: Incentives and moral justification for breaking the law - Moriconi Bezerra, Marcelo (Trends in organized crime, 2024)
Paraguay has become the main cannabis producer in South America and one of the largest exporters in the world. Some investigations about the cultivation of marijuana in the country portray a cruel environment in which peasants are exploited in “almost feudal” conditions by intermediaries who buy their crops at unreasonably low prices. However, a group of peasants who use the Mbaracayú Forest Nature Reserve as their labour area have created a safe and profitable ecosystem for developing their business. Based on interviews with key informants and visits to the area, the article describes the constraints and incentives that lead those peasants to engage in criminal activities, the strategies they have used to establish protective barriers, and the moral justifications that emerge as a result of their success in doing business. Although there are violent practices and extortion, we claim that the decision-making process to get involved in illegal markets is a free action influenced by alternative moral understandings that provide reasons and justifications for breaking the law. The moral map of these cannabis growers goes far beyond the mere economic justification of generating material resources and is related to economic, institutional, and social premises linked to a generalized aspiration of dignity and a life worth living. The functioning of informal institutions learned through previous interactions with state and non-state actors who regulate and protect the market, the perceived social approval/legitimation of the activity by referent groups, and the awareness of the capacity and skills necessary to successfully conduct the business have a crucial importance in the moral reformulation.